PENGARUH BARISTA TERHADAP SUASANA COFFEE SHOP MELALUI VARIABEL PRODUK - Prasetyo, Endro Dwi; Maulana, M. Teguh; Wachdijono, Wachdijono (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Consumers in this third marketing era want quality product conditions and a pleasant coffee shop atmosphere. The barista can create both of these conditions. This study aims to analyze the barista's influence on the coffee shop's atmosphere through product variables in the city of Cirebon. The research design was quantitative with a survey method, and the research location was determined deliberately, namely in the town of Cirebon, because there are many modern coffee shops in this city. The research population is coffee shop consumers in Cirebon City, whose number is unknown, so the sample size is determined based on a loading factor of 0.5, namely 120 respondents. The indicator measurement of each variable is a loading factor, using a Likert Scale and data analysis with the Structural Equation Modeling instrument. The study results concluded that the barista influences the atmosphere of the coffee shop through product variables in the city of Cirebon. The most dominant indicator for the barista variable is friendliness (0.84), for the coffee shop atmosphere variable, namely coffee shops and online marketing (0.75 each) and the product variable, the aroma of coffee drinks (0.75). To win the competition, it is recommended that coffee shop business actors improve the quality of these most dominant indicators.